Influence of Human Factors on Performance of Micro and Small Garment Enterprises in Ghana - Aidoo-Taylor , Bridgette; Otieno , Rose; Kinuthia , Lydia; Njonde , Veronica (African Journal of Education,Science and Technology (AJEST), 2024)
This study investigated how human factors affect the performance of micro and small garment enterprises in Ghana's Greater Accra region. The study was guided by human capital theory and resource-based view theory. A cross-sectional descriptive survey design was used to collect data from a varied population of garment entrepreneurs, association executives, and clients, with clustering, simple random, and purposive sampling approaches used. The study focuses on independent variables such as designers' expertise, attitude, and ability to manage their firms, with enterprise performance as the dependent variable. The data were analysed using descriptive and inferential statistics, as well as multiple linear regression, to determine variable correlations. The data show a large gender disparity among respondents, with females making up the majority of micro and small-scale textile industry owners. Moreover, a wide range of educational backgrounds were noted among respondents, with the majority holding diplomas. The study examined designers' attitudes and their impact on corporate performance, revealing different perspectives on entrepreneurial obstacles, market survival, client appeal, and business strategy. Despite varying perspectives, there is agreement on the significance of customer happiness and quality. A regression study shows a moderate association between human variables and enterprise success (R = 0.551, p < 0.001), with knowledge, aptitude, and enthusiasm showing substantial positive relationships. The study emphasizes the necessity of continual skill development and entrepreneurial education for designers to improve business performance. Overall, the findings indicate that designers in Ghana's micro and small garment-making firms are strongly committed to garment manufacturing, innovation, customer happiness, and quality, which has consequences for profitability and market success.